Annonaceae Family Alkaloids as Agents Against Leishmaniasis: A Review and Molecular Docking Evaluation - Lorenzo, Vitor P.; Scotti, Luciana; da Silva Almeida, Jackson R. G.; Scotti, Marcus Tullius (Current Drug Metabolism, 2020)
Leishmaniasis is a neglected disease that affects 15 million people worldwide. Existing treatments are associated with limitations, including high costs and toxicity. Several classes of natural substances have been reported to display leishmanicidal activity in the literature. Isoquinoline alkaloids, which are commonly found in the Annonaceae family, represent an important skeleton for the development of anti-leishmaniasis products. This study presents an overview of the potential use of Annonaceae alkaloids to treat leishmaniasis and describes a molecular docking study examining 215 isoquinoline alkaloids. All selected compounds contain a bisbenzyltetrahydroisoquinoline, suggesting the affinity of this skeleton for the target.
Keywords: docking